Molecular tools, potential frontiers for enhancing salinity tolerance in rice: A critical review and future prospective - Rasheed, Adnan; Li, Huijie; Nawaz, Muhammad; Mahmood, Athar; Hassan, Muhammad Umair; Shah, Adnan Noor; Hussain, Fiaz; Azmat, Saira; Gillani, Syed Faheem Anjum; Majeed, Yasir; Qari, Sameer H.; Wu, Ziming (Frontiers in Plant Science, 2022)
Improvement of salinity tolerance in rice can minimize the stress-induced yield losses. Rice (Oryza sativa) is one of Asia's most widely consumed crops, native to the subtropical regions, and is generally associated with sensitivity to salinity stress episodes. Salt tolerant rice genotypes have been developed using conventional breeding methods; however, the success ratio is limited because of the complex nature of the trait and the high cost of development. The narrow genetic base of rice limited the success of conventional breeding methods. Hence, it is critical to launch the molecular tools for screening rice novel germplasm for salt-tolerant genes. In this regard, the latest molecular techniques like quantitative trait loci (QTL), mapping, genetic engineering (GE), transcription factors (TFs) analysis, and clustered regularly interspaced short palindromic repeats (CRISPR) are reliable for incorporating the salt tolerance in rice at the molecular level. Large-scale use of these potent genetic approaches leads to identifying and editing several genes/alleles, and QTL/genes is accountable for holding the genetic mechanism of salinity tolerance in rice. Continuous breeding practices resulted in a huge decline in rice genetic diversity, which is a great worry for global food security. However, molecular breeding tools are the only way to conserve genetic diversity by exploring wild germplasm for desired genes in salt tolerance breeding programs. In this review, we have compiled the logical evidences of successful applications of potent molecular tools for boosting salinity tolerance in rice, their limitations, and future prospects. This well-organized information would assist future researchers in understanding the genetic improvement of salinity tolerance in rice.